Australia : Insurance Core Principles-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2012)
The insurance industry in Australia has weathered the global financial crisis well and was resilient to the catastrophic events in 2010/11. The insurance industry is mature but relatively small compared to the banking sector. Assets held by insurers represented only about 8 percent of the financial system total assets as at end-2011. Since 2007, the insurance market has been consolidating steadily as the total number of players fell from 190 to 172 although branches of foreign-owned general insurers rose from 36 to 43. The industry was comprised of 24 life insurers, 108 general insurers, 19 reinsurers, 7 captive general insurers and 14 friendly societies as at end-June 2011.